Blockchain technology and accounting - Berdikhojayeva, М.S.; Saduakasova, М.B.; Temirbekova , L.А. (BUKETOV BUSINESS REVIEW, 2019)
Data security and reliability are key issues that have to be addressed in the process of information exchange on the network. There are various technologies to ensure data reliability. One of the most promising is blockchain technology. The emergence of blockchain technology has led to the emergence of concerns in the profession of a certified accountant, which is completely understandable. Technological advances can threaten the employment of people in all professions. However, blockchain has implications for the accounting profession. First of all, a deep understanding of the principles of technology becomes one of the requirements for the profession. Then, as its spread and increasing incidence of the use of members of the profession need to clearly understand how the accounting rules are connected with this technology. The technology is based on an electronic distributed register of economic transactions and is very important for accountants and auditors because it provides great transparency. The article presents an analysis of the development of the use of distributed Ledger technologies (blockchain) in the field of accounting. The emphasis is made on the generalization and systematization of available data, the classification of the main stages of development of blockchain technologies is given, the forecasts of the use of blockchain technologies in the accounting of organizations are presented. This technology is expected to have an impact on accounting and auditing. But at that time, it can be argued that the accounting profession will continue to develop through the use of blockchain technology.